Sistema web para consulta e elaboração de listas de siglas, abreviaturas e acrônimos - Mezzalira, Cezar Augusto (2014)
The academic works, such as internship reports, monographs and thesis, ordinarily have lists of acronyms and abbreviations. These lists are composed of all terms (words) of this nature that are in the text and their respective description (meaning). The use of software to register acronyms and abbreviations reduce the time to elaborate these lists and the time to verify if the terms are described in the first use in the text. Thus, the result of this academic work is the development of a web system to storage this terms and its description. If this software is a web application, the terms registered can be used to compose lists of distinct academics works and by many people (students and teachers). Considering that the same term (acronym or abbreviation) can have distinct meaning, the system developed as a result of this work enable the indication of field and subfield, favoring the adoption of the meaning more appropriated to the term in the context of the area. The development was made using Java language with the interface created with components of PrimeFaces library.